Case Management for COVID-19 Pneumonia: Literature Review - Eka Nurhayati; Arum Pratiwi (Jurnal Berita Ilmu Keperawatan, 2020)
Introduction: Coronavirus is a collection of viruses that can infect the respiratory system. In many cases, this virus only causes mild respiratory infections, such as flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). The method is a literature review research in the form of case reports through the search of accredited journal sites such as Scientdirect and Elsevier with the keyword COVID-19 pneumonia in the period of 2015-2020. Research Results: in handling COVID-19 cases each country has its own way which consists of a physical examination, blood laboratory examination, chest CT scan, swab test, urine test, oxygen installation, mechanical ventilation, Extracorporeal Membrane Oxygention (ECMO) ), as well as the administration of drugs Ceftriaxone, Azithromycin, Piramivir, iopinavir-Ritonavir, Nafamostat and Intravenous Immune Globulin (IVIG), each patient differs based on history of illness. Conclusion: every region and every country has its own way of handling COVID-19 cases because until now there has been no definitive treatment or vaccine that can treat cases of COVID-19 that have struck all over the world.